2020
DOI: 10.1002/jbm.a.36971
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a contractile biomaterial from a decellularized spinach leaf without ECM protein coating: An in vitro study

Abstract: Myocardial infarction (MI) results in the death of cardiac tissue, decreases regional contraction, and can lead to heart failure. Tissue engineered cardiac patches containing human induced pluripotent stem cell‐derived cardiomyocytes (hiPS‐CMs) can restore contractile function. However, cells within thick patches require vasculature for blood flow. Recently, we demonstrated fibronectin coated decellularized leaves provide a suitable scaffold for hiPS‐CMs. Yet, the necessity of this additional coating step is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…To evaluate this point, we compared coated and non-coated TCPS and coverslips and showed that nuclear YAP location, YAP/TAZ protein level, cellular morphology and proliferation are unchanged between these two models (Supplementary Figure S3) suggesting that the role of coating was minimal in the context of this study and that the differences between coated stiff substrate and leaf were similar to what with we observed with non-coated TCPS and coverslips. This was confirmed by a recent study that showed that biofunctionalization was not required to promote cell contractility on decellularized spinach scaffolds and that no differences in contraction were found between coated leaves, coated TCPS, non-coated leaves, or non-coated TCPS at day 7 and 21 (Robbins et al, 2020). Cell culture on such scaffolds also modified cell response to external stimuli such as drug and radiation exposure.…”
Section: Discussionsupporting
confidence: 69%
“…To evaluate this point, we compared coated and non-coated TCPS and coverslips and showed that nuclear YAP location, YAP/TAZ protein level, cellular morphology and proliferation are unchanged between these two models (Supplementary Figure S3) suggesting that the role of coating was minimal in the context of this study and that the differences between coated stiff substrate and leaf were similar to what with we observed with non-coated TCPS and coverslips. This was confirmed by a recent study that showed that biofunctionalization was not required to promote cell contractility on decellularized spinach scaffolds and that no differences in contraction were found between coated leaves, coated TCPS, non-coated leaves, or non-coated TCPS at day 7 and 21 (Robbins et al, 2020). Cell culture on such scaffolds also modified cell response to external stimuli such as drug and radiation exposure.…”
Section: Discussionsupporting
confidence: 69%
“…Using moderate pressure and a PAA entrainer, the dissolving power of the fluid effectively removed plant cellular content to generate a biocompatible scaffold in mere hours. The gold standard chemical processing of plant material decellularization is time-consuming, taking several days (Table S1) 6,8,9,11,12,14 . Leaves are mechanically agitated in a bath of SDS/detergent for anywhere from 2 to 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not assess scaffold immunogenicity in this study, these results suggest that scCO 2 decellularization of vegetal material is indeed a non-toxic approach to provide biocompatible scaffolds for human cell culture. Several types of mammalian cells have been cultured on chemically decellularized vegetal scaffolds, including cancer cell lines, mesenchymal stem cells, mouse fibroblasts, human-induced pluripotent stem cell-derived cardiomyocytes, and more 6,8,9,11,12 . Although we foresee that scCO 2 decellularized scaffolds could also accommodate a diversity of cell types, additional investigations are required to confirm this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The creativity in utilizing different decellularized materials as cardiac scaffolds may best be exemplified by Gaudette et al, who utilize decellularized plants as a cardiac tissue scaffold. This “green” technology features decellularized spinach leaves, which are able to retain cardiomyocytes even without ECM coating [ 180 , 181 ].…”
Section: Treatments Based On Loading and Anisotropymentioning
confidence: 99%